HUBUNGAN TINGKAT PENDIDIKAN IBU DENGAN STATUS GIZI ANAK USIA 3-5 TAHUN DI PENDIDIKAN ANAK USIA DINI (PAUD) DI DESA BANYUURIP KECAMATAN KLEGO KABUPATEN BOYOLALI - Hantoko, Tri Yudhi; ., Sugihartiningsih (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
Abstract Background. The problem of malnutrition among children under five is now found in many developing countries, including Indonesia, is currently estimated to half the 100 million people of Indonesia or malnourished, but realized that nutritional factors can determine the quality of the nation. From the results of the preliminary survey the nutritional status nutritional status of children aged 3-5 years in Early Childhood Education (ECD) Banyuurip Village District Klego Boyolali when seen through nutritional status in terms of WHO-NCHS anthropometric assessment on the status of children get 70% normal and 30 % child malnutrition status. Objective. To determine the relationship between maternal education level with the nutritional status of children aged 3-5 years in Early Childhood Education (ECD) Banyuurip Village District Klego Boyolali. Research Methods. This study used a descriptive quantitative research study with the method of correlation with cross-sectional research design to obtain the relationship between the level of education Mother with child nutritional status aged 3-5 years. Sempel data from as many as 30 children. The variables studied were the level of maternal education and child nutritional status, and analyzed with a computer program SPSS. Results. The results of research show that there is a relationship between the level of maternal education with childrens nutritional status (p = 0.026). Level of closeness of the relationship between the two variables were moderate (p = 0.406) and berbading him straight. The higher the mothers education, the better the nutritional status of children aged 3-5 years who study in Early Childhood Education (ECD) Banyuurip Village District Klego Boyolali. Relationship ) of 0.406ï²between the two variables have a correlation coefficient ( with a significance or probability (p) of 0.026. P value <0.05 means that significant testing (H0 is rejected, Ha is accepted). Conclusion. There is a relationship between the level of maternal education and nutritional status of children. The higher the education the higher the mothers nutritional status. Keywords: child nutritional status, mothers education level